Feasibility Studies for the Measurement of Open-Charm Mesons at ALICE-3 Using Decay Channels with Neutral Mesons and Photons in the Final State - Mikhail Malaev; Victor Riabov (Particles, 2023)
ALICE-3 is being designed as a next-generation heavy-ion experiment to be operated at the high-luminosity Large Hadron Collider. With luminosities higher by a factor of fifty, ALICE-3 will be able to study5 properties of quark–gluon matter with probes and precision which were previously unavailable due to small cross sections, high background levels, and insufficient detector sensitivity. In particular, the properties of hot and dense QCD matter will be studied by measuring production cross sections, flow coefficients, azimuthal angular correlations and nuclear modification factors for open-charm hadrons. In this contribution, we present the results of feasibility studies for the measurement of ground and excited states of open-charm mesons in decay channels D0 → K− + π+ + π0, D*(2007)0 → D0 + γ and D*(2010)± → D0 + π± in pp, p-Pb and Pb-Pb collisions at LHC energies using the ALICE-3 experimental setup. We formulate the main requirements for the selection of particles and their combinations to ensure reliable signal extraction in a wide transverse momentum range and estimate the minimum size of the required data samples. The results obtained are also compared to previous findings for the open-charm measurements in different decay channels.